WOMEN’S RESISTANCE IN AMIN SALAMAH’S SHORT STORY “DAWLAT AZH-ZHULM SA’AH”: A LITERARY FEMINIST ANALYSIS - Fahira Zulfiani; Zulhelmi Zulhelmi; Suraiya Suraiya (Kafa`ah: Journal of Gender Studies, 2026)
This research study is grounded in the objective of identifying the forms of female resistance depicted in Amin Salamah's short story, Dawlat azh-Zhulm Sa’ah. The story portrays the social reality of a community still shaped by patriarchal systems, which generate gender inequality, manipulative seduction, social pressure, and slander against women. These circumstances drive women to enact resistance as a means of upholding their dignity and moral values, while simultaneously protecting themselves and their families. This research adopts a qualitative approach, utilizing textual content analysis techniques. The data comprise narrative excerpts and dialogues that reflect the attitudes and actions of female characters when confronted with social pressures. The analysis is conducted through the lens of Naomi Wolf's power feminism, which foregrounds the concepts of personal power and agency, and is further enriched by the integration of Islamic values as a moral and spiritual framework for comprehending women's resistance. The findings indicate that female resistance is manifested through the rejection of gender stereotypes, assertiveness in safeguarding personal honor against male desire, spiritual resistance to slander through prayer, and proactive efforts to shield the family from detrimental social influences. These findings emphasize that the female characters are not portrayed as passive victims; rather, they emerge as conscious agents endowed with the strength to oppose behaviors that conflict with moral principles and Islamic teachings, all in the service of preserving their dignity and honor. This study contributes to the broader discourse on Arabic literary feminism by integrating the power feminism perspective with Islamic values to illuminate the complexity of female agency.